PERTUMBUHAN STEK BATANG GMELINA ARBOREA HASIL KOLEKSI DARI LIMA POPULASI SEBARAN DI INDONESIA - Hamdan Adma Adinugraha; Dedi Setiadi; Arnoldus Naibini; Nyuwito Nyuwito (Jurnal Pemuliaan Tanaman Hutan, 2020)
This study was conducted to determine the effect of plant material origin and size of cuttings on the growth ability of Gmelina. arborea stem cuttings in the nursery. The study was arranged in a randomized factorial pattern design, consisting of two factors, namely the length of the cuttings (L1 = 20 cm and L2 = 30 cm) and the cuttings size factor (small diameter class/D1 = <1.25 cm, medium/D2 = 1.25 – 2.50 cm and large/D3 => 2.50 cm). Each treatment used 5 stem cuttings and repeated in 3 times, which are grouped based on their origin population namely Bantul/P1, Bogor/P2, Lampung/P3, Bondowoso/P4 and Lombok/P5. The observationsshowed the survival percentage was 83.12% and the rooting percentage was 78.23% which was influenced by the length and diameter of the stem cuttings. The growth of shoots (number, length and diameter) and the number of shoot nodes and leaf were affected by the interaction of origin of the population and the length and diameter of the stem cuttings. Applying stem cutting method is very potential to produce planting stock of Gmelina arbore. Stem cuttings which has a biger size showed better grow of stem cuttings.